α-1 Adrenoceptor Activation in the Dorsal Raphe Nucleus Decreases Food Intake in Fasted Rats - Flores, Rafael Appel; Dos-Santos, Raoni Conceição; Steinbach, Renata; Rodrigues-Santos, Isabelle; de Jesus, Aline Alves; Antunes-Rodrigues, José; Paschoalini, Marta Aparecida (Frontiers in Physiology, 2021)
The dorsal raphe (DR) nucleus is involved in a myriad of physiological functions, such as the control of sleep-wake cycle, motivation, pain, energy balance, and food intake. We have previously demonstrated that in ad libitum fed rats the intra-DR administration of phenylephrine, an α-1 receptor agonist, does not affect food intake, whereas clonidine, an α-2 receptor agonist, potently stimulates food intake. These results indicated that in fed rats an increased adrenergic tonus blocked food intake, since the activation of α-2 auto-receptors, which decreases pre-synaptic release of adrenaline/noradrenaline, affected food intake. Thus, in this study we assessed whether the response to adrenergic stimuli would differ after overnight fasting, a situation of low adrenergic activity in the DR. Intra-DR administration of adrenaline and noradrenaline blocked food intake evoked by overnight fasting. Similarly, phenylephrine administration decreased hunger-induced food intake. These changes in food intake were accompanied by changes in other behaviors, such as increased immobility time and feeding duration. On the other hand, intra-DR administration of clonidine did not affect food-intake or associated behaviors. These results further support the hypothesis that in fed animals, increased adrenergic tonus in DR neurons inhibiting feeding, while in fasted rats the adrenergic tonus decreases and favors food intake. These data indicate a possible mechanism through which adrenergic input to the DRN contributes to neurobiology of feeding.